An IFC-inspection process model for infrastructure projects: Enabling real-time quality monitoring and control - Ding, L.; Li, K.; Zhou, Y.; Love, Peter (Elsevier BV, 2017)
© 2017 Elsevier B.V. Comprehensive and timely inspection of quality issues is critical for reducing rework and delays in infrastructure projects. Enabling a real-time quality checking guidance system to be used in practice requires formal data exchange methods and inspection process control. This, however, remains an on-going challenge, as information is often expressed in different data representations and stored in disparate locations and formats. There have been a limited number of studies that have examined the relationship among physical objects, schedule, and quality management information related to the process of inspection as well as the difficulties associated with enabling real-time monitoring and control of quality. In addressing this issue, a design science research approach is used to develop and apply an Industrial Foundation Classes-based Inspection Process Model (IFC-IPM) to enable information exchange requirements for quality-related information to occur in real-time during construction. Within the IFC-IPM schema and extension that is developed, a physical, schedule, and quality management model exist. The IFC-IPM extension defines the dynamic property sets that form part of quality management system. The dynamic property set of the schedule can identify inspection codes, time, and its content. This provides inspectors with the ability to undertake real-time quality monitoring and control. The IFC-IPM that is developed is applied to a real-life subway infrastructure project. It is demonstrated that the developed IFC-IPM provides an effective platform for data sharing and exchange of quality related information and other IFC-compliant applications. The model can be used to streamline the quality management process as it reduces the time to attend to undertake rework and increases the accuracy and timeliness of inspections and the acceptance of activities and products.